PRODUCT BRANDING TRANSFORMATION IN THE DIGITAL AGE: STRATEGY, IDENTITY, AND CONSUMER LOYALTY FOR MSMEs - Kadeni Kadeni; Tehedi (INJOSEDU: International Journal of Social and Education, 2026)
This article analyses the transformation of SME product branding in the digital era, focusing on digital-first strategies, brand identity strengthening, and their impact on consumer loyalty. The results show that strategies such as content marketing, influencer collaboration, e-commerce live streaming, and personalised SEO increase visibility by up to 60% and ROI by 5:1, while a cohesive digital brand identity—through authentic visual elements, local storytelling, and the Aaker model—accelerates loyalty through the Oliver stage with a 20-point increase in NPS, 40% retention, and 2x CLV. Practical implications include a 6-12 month roadmap for SMEs to compete in Indonesia's Rp 2,000 trillion digital economy by 2030, with recommendations for government-academic collaboration to address the digital literacy gap.